NEEDS FOR SECONDARY SCHOOL MANAGEMENT BASED ON THE CONCEPT OF CREATORS OF POSITIVE CHANGES - Vejjavanit, Thanapuwadon; Charoenkul, Nantarat; Siribanpitak, Pruet (Journal of Educational Review Faculty of Education in MCU, 2025)
This research aimed to: 1) investigate the current and desired states of secondary school administration based on the concept of positive change agents, and 2) identify the priority needs for its development. The study employed a survey research design. The population comprised 2,085 secondary schools under the Office of the Basic Education Commission, and a sample of 324 schools was selected using multi-stage sampling. A total of 972 key informants participated, including school directors or deputy directors, heads of academic departments, and heads of student affairs or responsible teachers. The research instrument was a structured questionnaire focusing on perceptions of current and desired states of administration aligned with the concept of positive change agents. Data analysis involved descriptive statistics frequency, percentage, mean, standard deviation and the Modified Priority Needs Index (PNImodified). The research findings reveal that: 1) The current conditions of secondary school administration based on the concept of positive change agents, when classified by academic administration, were found to be at a high level overall. When examining each aspect, the highest mean was found in curriculum implementation evaluation, followed by school curriculum design and development and teaching and learning process development. When classified by the concept of positive change agents, the overall condition was also at a high level. For student affairs, the current condition was also found to be at a high level overall. When classified by the concept of positive change agents, the aspect with the highest mean was the power of self-discovery, followed by the desire to transform society, and perseverance and resilience in overcoming obstacles to achieve goals. Regarding the desirable conditions of secondary school administration based on the concept of positive change, when classified by academic administration, the overall level was found to be at the highest level. The subsequent aspects were the desire to transform society and perseverance and resilience in overcoming obstacles to achieve goals. For student affairs, the desirable condition was found to be at the highest level overall. When examining each aspect, the highest mean was in the definition of the scope of daily activity arrangements, followed by the organization of co-curricular and extracurricular activities, and the integration of activities through hands-on practice, respectively. 2) The needs for the development of secondary school administration based on the concept of positive change, when classified by academic administration, revealed that the highest need was the implementation of the curriculum in classroom teaching, followed by the development of the teaching and learning process, such as teacher training, evaluation of school curriculum implementation, and school curriculum development, respectively. For student affairs, the highest need was the integration of activities through hands-on practice, followed by the organization of co-curricular and extracurricular activities, and the definition of the scope of daily activity arrangements, respectively. When classified by the concept of positive change, the highest need was found to be the power of self-discovery, followed by the desire to transform society, and perseverance and resilience in overcoming obstacles to achieve goals, respectively.